Formation and characterization of high-performance silicon thin-film transistors with and without location-controlled grain boundary. (12th September 2017) - Liao, Chan-Yu; Lin, Hsiao-Chun; Wang, Chao-Lung; Lee, I-Che; Chou, Chia-Hsin; Li, Yu-Ren; Cheng, Huang-Chung
Abstract: This paper reports the demonstration of structural effects on excimer laser crystallization (ELC) for the Si strip with a recessed-channel structure on the silicon nitride under-layer (RCS-ULN). We revealed that a single location-controlled grain boundary (GB) oriented normal to the Si strip in the middle site without any other GB in the recessed region can be attained via ELC for the RCS-ULN structures with a short recessed region between neighboring long thick regions in a narrow Si strip. This can be attributed to the effective production of a significant 2D lateral thermal gradient in the recessed region and neighboring thick regions. Consequently, the RCS-ULN TFTs fabricated at the position one-half of such an optimal recessed region can achieve a superior field-effect mobility of 670 c m 2 V − 1 ⋅ s − 1 with minor performance variations since the single-crystal-like Si channel has been adopted.